KONFLIK KRISTEN-MUSLIM (STUDI KASUS PENOLAKAN PEMBANGUNAN GEREJA KRISTEN INDONESIA BERBAH, SLEMAN, YOGYAKARTA) - , dafcoriza ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Conflict phenomena happening on GKI Pos Adisucipto in Berbah District of Sleman â Yogyakarta about rejection of the church is part of negotiation among two religious groups, Muslim â Kristen, and it faces process of adaptation towards the appearance of Christians as new comer in this area. The difference of perception of each group became factor of lack in term of communication leading religious conflict in between. The dilemma of GKI Pos Adisucptoâs member that is not allowed to build worship house is one of the social instrument that shows significantly that rejection on the church in this area, Berbah district, is categorized as conflict. This is due to religious violence. The definition of conflict itself is the relation in two or more, whether individual or group that feel to have the controversial aim (Christ Mitchell, The Structure of International Conflict, Macmillan, London, 1981). If the appearance of conflict within society is ignored constantly it will potentially cause violence among these groups. The conflict also causes violence either physically or non-physically. By this assumption, conflict happening among society structure will reach violence. The result of this study has shown that factors leading conflik of GKI Pos Adisucipto is not only about religious factors but also cultural values among society. The lack of inter-religious pluralism values sometimes becomes barrier in religious life of Indonesian society. Several findings which were founded in this research have important contribution that in the future could be able to be guideline of conflict resolution in Indonesia. The efforts that have been made in stemming conflict rejection in building GKI Pos Adisucipto in this study were: (1) Negotiation: The dialogue between the two sides (Muslim - Christian), (2) Cultural Approach, (3) Structural Approach, in relation to conflict of GKI Pos Adisucipto between the two parties actually, they want the situation in each village to solved after holding a variety of mediation between the church and those who opposed the church. Reconciliation efforts in the case are initiated by the church as them as 'objects' in the ongoing conflict.